Caribbean Report 02-03-1995 - Crosskill, Hugh (anchor); Morris, Chris (correspondent); Cuffy, Victor (interviewee); Smith, Clifford (correspondent); Hayes, Rosie (correspondent); Dausa, Rafael (interviewee); Villarroel, Gustavo (interviewee); Fraser, Tony (correspondent); Brown, Hazel (interviewee); Nguyen, Hong Trang (interviewee) (The British Broadcasting Corporation, 1995)
The International Narcotics Control Strategy Report compiled by the United States State Department accuses the government of St. Vincent and the Grenadines of not doing enough to crack down on drug trafficking. The State Department refers to persistent reports of narcotics-related corruption in senior levels of St. Vincent's government. Victor Cuffy, Head of the island's Human Rights Committee gives his reaction to the report. A delegation of West Indies Rum and Spirits Producers' Association (WIRSPA) lobbies to abolish the European Union quotas on imports of rum. Cuban diplomat, Jose Martinez, the First Secretary at the Cuban Embassy in Kingston, has defected. Rafael Dausa, official spokesman of the Cuban Foreign Ministry confirmed the defection and called Martinez a traitor. Rosie Hayes speaks to Gustavo Villarroel on the concerns about defections in Cuba's sporting world as the Pan American Games approach. Women's rights and the debt burden of the English-speaking Caribbean are among the issues to be discussed by regional non-governmental organizations (NGOs) at the Social Summit to be held in Copenhagen, Denmark.
1. Headlines with Hugh Crosskill (00:00-00:33)
2. US State Department accuses the government of St. Vincent and the Grenadines of not doing enough to crack down on drug trafficking (00:34-02:44)
3. Victor Cuffy gives his reactions to the US State Department report (02:45-06:11)
4. WIRSPA delegation campaign to abolish the European quotas on the import of rums (06:12-08:51)
Keywords: Drug traffic -- Saint Vincent and the Grenadines; Drug traffic -- Caribbean Area; Marijuana industry -- Saint Vincent and the Grenadines; Political corruption -- Caribbean Area; Saint Vincent and the Grenadines -- Economic conditions; Rum industry -- Caribbean Area; Import quotas -- European Union countries; European Union countries -- Economic policy; Diplomats -- Cuba; Diplomatic and consular service, Cuban -- Jamaica; Defectors -- Cuba; Sports and state -- Cuba; Sports -- Cuba; Defection -- Cuba; Women's rights -- Caribbean Area; Women -- Caribbean Area -- Social conditions; Poverty -- Caribbean, English-speaking; Poverty -- International cooperation; Non-governmental organizations